ANALISIS PENINGKATKAN KEMAMPUAN MANAJERIAL PEGAWAI NEGERI SIPIL - Tobar - (Sekolah Tinggi Ilmu Ekonomi Gentiaras, 2016)
Local Government Employees managerial ability is quite high. But there are someemployees who have managerial ability is low, especially the ability in terms of knowledge, a senseof responsibility to the job, and speed in serving the community, while job satisfaction is generallyhigh, but fellow employees is less encouraging, so it will have an impact on satisfaction they.Managerial capabilities affect the performance of employees, if the managerial ability isapplied with a load of their duties, then they will feel satisfied in their work, so it will improveperformance. Job satisfaction affect the performance of employees, if the employees are satisfied intheir work will strive to achieve good performance. Managerial capabilities and job satisfaction affectthe performance of employees, partially dominant managerial abilities affect the performance of theemployee job satisfaction.